Immigration and regional integration in a globalizing world : myths and truths about migration - White, Christopher, 1978- (Lexington Books, 2015)
"White uses an evidence-based approach to understanding immigration and economic integration to debunk the "migration myth"" that sees a strong connection between these two factors. Contrary to prevailing assumptions, the main argument is that there is no substantial relationship between the international migration and regional integration, despite the political rhetoric that generates enormous fear and anxiety surrounding these issues. Instead of conflating them, countries can consider the benefits of integration policies without worrying about migration and can consider migration policies without concern for integration. This book is for anyone concerned about the issue of immigration and its relationship to trade liberalization and regional integration."--Publisher's website.